Health benefits of Quran memorization for older men. (9th November 2017) - Saquib, Nazmus; Saquib, Juliann; Alhadlag, Abdulrahman; Albakour, Mohamad Anas; Aljumah, Bader; Sughayyir, Mohammed; Alhomidan, Ziad; Alminderej, Omar; Aljaser, Mohamed; Al-Dhlawiy, Ahmed Mohammed; Al-Mazrou, Abdulrahman
Objective: To examine the association between Quran memorization and health among older men. Methods: This cross-sectional study included older Saudi men (age ≥ 55 years) from Buraidah, Al-Qassim. The neighborhoods were selected randomly (20 out of 96); eligible men from the mosques were recruited. Demographics, lifestyle, and depression were assessed with standardized questionnaires; height, weight, blood pressure, and random blood glucose (glucometer) were measured with standard protocol. Results: The mean and standard deviation for age, body mass index, and Quran memorization were 63 years (7.5), 28.9 kg/m 2 (4.8), and 4.3 sections (6.9). Prevalence of hypertension, diabetes, and depression were 71%, 29%, and 22%, respectively. Those who memorized at least 10 sections of Quran were 64%, 71%, and 81% less likely to have hypertension, diabetes, and depression compared to those who memorized less than 0.5 sections, after controlling for covariates. Conclusion: There was a strong linear association between Quran memorization and hypertension, diabetes, and depression indicating that those who had memorized a larger portion of the Quran were less likely to have one of these chronic diseases. Future studies should explore the potential health benefits of Quran memorization and the underlying mechanisms.